Decision support system for selection of exemplary students using the analytical hierarchy process (AHP) method - Susana Dwi Yulianti; Rini Nuraini; Mohammad Imam Shalahudin; M. Hadi Prayitno (Jurnal Teknik Informatika C.I.T Medicom, 2023)
The problem that occurs in determining exemplary students is the length of the process of determining the assessment of exemplary students, this is due to the fact that each teacher must first select potential exemplary students. After obtaining the names of prospective new model students, the selection of model students is carried out by an assessment team from the school. The purpose of this study is to select exemplary students at the end of each semester using the Analytical Hierarchy Process method. Based on the results of the assessment using the Analytical Hierarchy Process method, the first model student was obtained by Budi Riantono with a value of 0.250949, the second model student was obtained by Putri Azzahra with a value of 0.235755, the third model student was obtained by Akhmad Wijayanto with a value of 0.204881. The results of calculations between manual calculations and calculations using a web-based application show no difference in value and ranking. Then a web-based application is made based on the results of manual calculations using the Analytical Hierarchy Process method that has been made.